Determinants of efficiency in the Malaysian banking sector: does bank origins matter? - Sufian, Fadzlan; Kamarudin, Fakarudin; Md Nassir, Annuar (Elsevier, 2016)
The paper follows Simar and Wilson's (2007) two-stage procedure to analyze the efficiency of the Malaysian banking sector. In the first stage, we employ the bootstrap Data Envelopment Analysis (DEA) method to compute the efficiency of individual banks during the period 1999–2008. We then use bootstrap regression to examine the impact of origins on bank efficiency, while controlling for the potential influence of contextual variables. The DEA results indicate that the Malaysian banking sector has exhibited increase in efficiency over the sample period. We find that banks from the Asian countries to be relatively more efficient compared to foreign banks from other regions and their domestic bank peers. In essence, the empirical evidence rejects the home field advantage hypothesis, but lends support to the “limited form” of the global advantage and the liability of unfamiliarness hypotheses.